Solve for x
4(2x+3)=-6+5x
2 answers:
Answer:
x = -6
Step-by-step explanation:
4(2x+3)=-6+5x
Multiply the bracket by 4
(4)(2x)(4)(3)=-6+5x
8x+12=5x-6
Move 5x to the other side. Sign changes from +5x to -5x.
8x-5x+12=5x-5x-6
8x-5x+12=-6
3x+12=-6
Move 12 to the other side. Sign changes from +12 to -12.
3x+12-12=-6-12
3x=-18
Divide by 3 for both sides
3x/3=-18/3
Cross out 3 and 3, divide by 3 and then becomes x
x=-6
Answer: x=-6
You might be interested in
She puts 11 pieces of fruit into each bag.
Multiply this by the number of people going on the trip
Answer: x=-1 is the answer
Step-by-step explanation:
-6 is greater than 5 is wrong
Answer:
0 because it fell apart after he glued it togheter
Step-by-step explanation:
Answer:
She can fit either the 16 video clips or the two movies
Step-by-step explanation: